The Influence of Glyserol as Plasticizer in Physical Properties of Bioplastic from Bread Fruit Starch - Lulu Nurdini I; Dini Holipah; Rida Magfira Maulidina (Seminar Nasional Teknik Kimia Kejuangan, 2017)
The main aim of this study was to identify the influence of plastisizer and the potensial use of bread fruit starch, Artocarpus altilis, as the raw material for synthesis of bioplastic film. Chitosan was added to make bioplastic more elastic. Film was cast from heated bread fruit starch (5 g), chitosan solution (in 0,5 ml acetic acid solution in 50 ml aquadest) and glycerol (0,3 ml, 04 ml, 0,5 ml, 0,6 ml, 0,7 ml) at 740C and stired well at 160 rpm until gelatinisation formed. Physical properties of bioplastic was characterised. The result showed that tensile strenght of bioplastic was 1,667 kgf/mm2(0,3 ml glycerol) higher than the other variation of glycerol and the percent of elongation was 4,923%. The biodegradability test for 8 weeks showed bioplastic degraded naturally